Gnostic Metaphysics in the Dynamics of Foxian Light and the Reunion of the Soul with God - Reynolds, Glenn H. (Quaker studies, 2006)
This paper analyses prior scholarship surrounding the emphasis upon, and interpretation of, the moral and ethical dynamic within the Light theology of George Fox, and advances it by suggesting a metaphysical approach which is remarkably similar to that found in Christian (Valentinian) Gnosticism. This similarity is particularly illustrated in an examination of Fox's theology pertaining to the nature and disposition of the divine soul and its reunion with God.